I'm a Manatee - Lithgow, John. (New York Simon & Schuster Books for Young Readers, 2003)
A boy imagines that he is a manatee, sprinkling seaweed on his Raisin Bran-atee and dignifying his watery domain with his wit, sophistication, and urbanity. Includes CD and score.
Keywords: Manatees - Fiction; Imagination - Fiction; Stories in rhyme